CO2 Cryotherapy Combined with Kushen Gel for the Treatment of Chronic Cervicitis: A Real-World Study - Lina Zhang; Yilu Zhou; Jiaxin Liu; Yiqing Lai; Wenjun Pan; Xianzhen Xin; Mohan Xiao; Su Lu (Clinical and Experimental Obstetrics & Gynecology)
Background: This real-world study aims to investigate clinical efficacy and safety of CO2 cryotherapy combined with Kushen gel for chronic cervicitis. Methods: From June 2021 to December 2021, a total of 363 patients with chronic cervicitis treated in the Center for Diagnosis and Treatment of Cervical Diseases were selected. A total of 208 patients were treated with CO2 cryotherapy combined with Kushen gel, while 155 cases only received cervical CO2 cryotherapy. Results: The total effective rate of combined therapy for chronic cervicitis was 100%, with a higher cure rate than CO2 cryotherapy alone (p = 0.004), and it was significantly correlated with the degree of cervical inflammation (p <0.050). Cure rate increased with decreasing severity of inflammatory response. Conclusions: CO2 cryotherapy combined with Kushen gel for chronic cervicitis has definite clinical efficacy with few adverse reactions and the combined treatment of CO2 cryotherapy with Kushen gel could enhance the therapeutic effect.